Membangun Brand Loyalty: Analisis Peran Brand Equity Dan Brand Trust Pada Dua Merek Mie Cup Terpopuler Di Solo Raya - Nisa, Pramesti 'Ainun; Nasir, Moechammad (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
This study proposes a model that explores the influence of brand equity elements, namely brand awareness, brand association, perceived quality on brand loyalty, with brand trust as an intervening variable, on the two most popular cup noodle brands in Solo Raya, namely Mie Sedaap Cup and Pop Mie. This research was conducted to find out the differences in the impact of brand equity elements on brand trust and brand loyalty in each brand. This study uses an explanatory research method with a purposive sampling approach. This study involved 223 respondents who met the criteria. The data was processed using SmartPLS version 3.0. The results showed that perceived quality has a significant influence on brand trust and brand loyalty in both brands. However, brand awareness only has a significant influence on brand trust and brand loyalty on Sedaap Cup Noodles. Meanwhile, brand association only has a significant effect on brand trust and brand loyalty on Pop Mie. Brand trust is able to mediate the relationship between perceived quality and brand loyalty on both brands, but brand trust is unable to mediate the effect of brand association on brand loyalty on Sedaap Cup Noodles and brand trust is unable to mediate the effect of brand awareness on brand loyalty on Pop Mie.